Investigating the impacts of climate services among commercial and smallholder farmers to improve the uptake of climate information - Nyudwana, Sinazo (Department of Environmental and Geographical Science, 2024)
Climate change has impacts on agricultural production through changes in precipitation, temperature, carbon dioxide fertilisation, surface water runoff, and climate variability. These changes affect the ability of a region's agricultural sector to sustain production. South Africa is particularly vulnerable because of poverty, food insecurity, and a low adaptive capacity. Therefore, there is a crucial need for adaptation in the agricultural sector, which requires sufficient climate information to achieve strong climate-resilient development. This research aims to assess how the uptake of climate information can be improved with climate services among commercial and smallholder farmers in South Africa. In this study, a total of 29 respondents were interviewed. These respondents consisted of a seasonal climate forecast provider, two agricultural advisors and 13 Western Cape and Eastern Cape farmers who were a representation of the two main farming systems in South Africa. The interview questions for the seasonal climate forecast provider and agricultural advisors obtained information on the rate of access to and use of climate services, as well as extension support and engagement. The farmer interview questions were designed to elicit farmers' perspective on climate risks, as well as access to and use of climate services, such as seasonal climate forecasts, in agricultural decision-making. According to the results of this study, farmer-researcher engagement and extension support is currently poor. This is demonstrated by the low response rate of 8% of commercial and smallholder farmers who reported using extension services, as well as a lack of awareness and understanding of seasonal climate forecasts. Furthermore, access to climate services and the use of seasonal climate forecasts differed among commercial and smallholder farmers, with 46% of commercial farmers with access but limited use due to lack of trust. In contrast, smallholder farmers had no access and usage due to a lack of awareness and understanding of seasonal climate forecasts. Additionally, the results revealed that both the commercial and smallholder farmers considered networks as an essential enabler to use seasonal climate forecasts. The networks mentioned were the local farmer groups and agricultural co-ops such as GrainSA and Overberg Agri. This research, therefore, recommends improving farmers' knowledge of seasonal climate forecasts through training and the development of accessible, context-specific climate services. Moreover, the dissemination and interpretation of seasonal climate forecasts by local agricultural advisors and extension officers is recommended. This will assist in the improved uptake of climate information and more active engagement among seasonal climate forecast producers, agricultural advisors, agricultural extension officers, and farmers. viii Keywords: Climate services; Seasonal climate forecasts; Commercial farmers; Smallholder farmers; South Africa